A novel 3-dimensional electromagnetic guidance system increases intraoperative microwave antenna placement accuracy. Issue 12 (December 2017) - Sastry, Amit V.; Swet, Jacob H.; Murphy, Keith J.; Baker, Erin H.; Vrochides, Dionisios; Martinie, John B.; McKillop, Iain H.; Iannitti, David A.
Abstract: Background: Failure to locate lesions and accurately place microwave antennas can lead to incomplete tumor ablation. The Emprint™ SX Ablation Platform employs real-time 3D-electromagnetic spatial antenna tracking to generate intraoperative laparoscopic antenna guidance. We sought to determine whether Emprint™ SX affected time/accuracy of antenna-placement in a laparoscopic training model. Methods: Targets (7–10 mm) were set in agar within a laparoscopic training device. Novices (no surgical experience), intermediates (surgical residents), and experts (HPB-surgeons) were asked to locate and hit targets using a MWA antenna (10-ultrasound only, 10-Emprint™ SX). Time to locate target, number of attempts to hit the target, first-time hit rate, and time from initiating antenna advance to hitting the target were measured. Results: Participants located 100% of targets using ultrasound, with experts taking significantly less time than novices and intermediates. Using ultrasound only, successful hit-rates were 70% for novices and 90% for intermediates and experts. Using Emprint™ SX, successful hit rates for all 3-groups were 100%, with significantly increased first-time hit-rates and reduced time required to hit targets compared to ultrasound only. Discussion: Emprint™ SX significantly improved accuracy and speed of antenna-placement independent of experience, and was particularly beneficial for novice users.